Genomic Confirmation of Resistance Genes for Blast, Bacterial Leaf Blight, Rice Tungro Spherical Virus, and Brown Planthopper in Tropically Adapted Temperate Japonica Rice Varieties - Pacleb, Myrish Alvarez; Lee, Seongkyeong; Hechanova, Sherry Lou; Padolina, Thelma; Pautin, Lenie; Del-Amen, Jesson; Park, Dong-Soo; Choi, Il-Ryong; Kim, Sung-Ryul; Shin, Dongjin; Suh, Jung-Pil (Agronomy (Basel), 2025)
The Rural Development Administration (RDA) of the Republic of Korea, in collaboration with International Rice Research Institute (IRRI), developed six temperate japonica rice varieties—MS11, Japonica 1, 2, 6, 7, and Cordillera 4—which were officially approved for release in tropical environments. These varieties offer improved eating quality, enhanced lodging resistance, and increased market value. Although initial evaluations indicated that the varieties were resistant to moderately resistant to major biotic stresses, recent field trials revealed a gradual increase in susceptibility over time. To address this, we conducted comprehensive evaluations of these varieties against rice blast under both greenhouse and field conditions and assessed their responses to bacterial leaf blight (BLB), rice tungro spherical virus (RTSV), and brown planthopper (BPH) under controlled environments. Additionally, whole-genome sequencing was employed to confirm the presence of known resistance alleles. Our findings revealed variable resistance profiles across the six varieties. Japonica 1 exhibited the most stable resistance to blast, supported by the presence of the Pi5 allele. Japonica 7 showed strong resistance to key BLB isolates and moderate resistance to a broader range of Xoo races, supported by the resistant Xa25/OsSWEET13 haplotype. In addition, Japonica 7, along with Japonica 6, carried the tsv1 gene for RTSV resistance. However, none of the six varieties possessed other major resistance genes for BPH. These results highlight the urgent need to introgress durable resistance genes into tropical japonica rice to enhance resilience and broaden the spectrum of biotic stress resistance—critical traits for sustainable rice production in tropical environments.